Lead Structures for New Antibacterials: Stereocontrolled Synthesis of a Bioactive Muraymycin Analogue. Issue 47 (15th October 2014) - Spork, Anatol P.; Büschleb, Martin; Ries, Oliver; Wiegmann, Daniel; Boettcher, Stefan; Mihalyi, Agnes; Bugg, Timothy D. H.; Ducho, Christian
Abstract Naturally occurring muraymycin nucleoside antibiotics represent a promising class of novel antibacterial agents. The structural complexity suggests the investigation of simplified analogues as potential lead structures, which can then be further optimized towards highly potent antimicrobials. Herein we report studies on muraymycin‐derived potential lead structures lacking an aminoribose motif found in most naturally occurring muraymycins. We have identified a 5′‐defunctionalized motif to be ideal in terms of stability and chemical accessibility and have synthesized a full‐length muraymycin analogue based on this structure using a novel fully stereocontrolled route. The obtained 5′‐deoxy analogue of the natural product muraymycin C4 showed good inhibitory properties towards the bacterial target protein MraY, sufficient pharmacokinetic stability and no cytotoxicity against human cells, thus making it a promising lead for antibacterial drug development.